Analisis Kesulitan Menulis Permulaan Pada Siswa Kelas II Sekolah Dasar - Ayu Rizki Amalya; Amalia Kartika Lubis; Elsika Riantina Putri; Putri Rahmadhani Nasution (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Early writing skills are a basic skill that supports the literacy development of elementary school students. However, some second-grade students still experience difficulties in mastering these skills. This study aims to analyze early writing difficulties, the contributing factors, teachers' efforts to overcome them, the role of parents, and the learning process of early writing in second-grade elementary schools. The study used a qualitative method with a descriptive approach. Research informants consisted of second-grade teachers, students, principals, and parents. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing. The results showed that students experienced difficulties in forming letters, distinguishing similar letters, writing simple words and sentences, using capital letters and punctuation, and maintaining neatness of writing. These difficulties were influenced by internal factors, such as fine motor skills and learning motivation, as well as external factors, such as lack of practice and parental guidance. Teachers addressed these difficulties through gradual practice, the use of engaging learning media, individual guidance, and ongoing evaluation. This study concluded that collaboration between teachers, parents, and schools is an important factor in improving early writing skills and provides a basis for developing more effective learning strategies.